Isolation of Potential Azo dye Degrading/Tolerating Bacteria from Polluted Environment - Mehzabin, Monira; Ahsan, Sunjukta (Bangladesh Journal of Microbiology, 2024)
Various industries including the food and textile industries result in the release of azo dyes into the environment. These dyes are known to exert toxic effects on humans, animal and plants. Biological methods of azo dye bioremediation is a solution for the detoxification of azo dye in the environment. The present study was undertaken to isolate bacteria with potential for azo dye bioremediation. From five polluted environment samples, eight bacteria were isolated in azo dye supplemented Nutrient agar. Six isolates (75%, n=8) decolorized azo dye completely following 24 hours of incubation. The control tube with no bacterial inoculation remained blue, indicating that only microbial biotransformation processes were taking place. In each case, a blue-colored ring remained at the top, indicating the anoxic nature of the dye decolorization process. All isolates grew in presence of 400 ppm, 60% tolerated 600 ppm and 20% tolerated 800 ppm, whereas 1000ppm was inhibitory for growth of all isolates. Dead autoclaved cells of three representative isolates were tested for biosorption potential. Only one isolate turned the methylene blue supplemented nutrient broth colorless. This explains that this isolate was not metabolizing methylene blue rather it bound the dye to the cell structure. Two isolates did not show biosorption abilities indicating that their mechanism of bioremediation was enzymatic reduction. 16s rDNA sequencing identified two of the isolates as Lysinibacillus capsici and Stenotrophomonas muris. Bangladesh J Microbiol, Volume 40, Number 2, December 2023, pp 56-59